Who Is Coming to the Artefactual Field Experiment? Participation Bias among Chinese Rural Migrants - Paul Frijters; Tao Sherry Kong; Elaine M. Liu (Institute for the Study of Labor (IZA), 2015)
In this paper, we compare participants in an artefactual field experiment in urban China with the survey population of migrants from which they were recruited. The experimental participants were more educated, more likely to lend money to friends, and worked fewer hours than the general population. They differ significantly from non-participants in terms of regression coefficients, such as the effects of wealth and marital status on the probability of being self-employed and distance migrated. We thus find that there was selection into our experiments on the basis of both observable characteristics and on unobserved differences in behavioral relations.
Keywords: C81; C93; C90; 330; artefactual field experiment; participation bias; rural migrants